Framework To Mitigate the Challenges Affecting Construction Sector Smes Readiness to Adopt Ghaneps: Mitigating Challenges in Construction Sector SMEs (Journal of Science and Technology, 2025)
The Government of Ghana is leveraging the growth of Information and Communication Technology (ICT) to launch the Ghana Electronic Procurement System (GHANEPS) to improve the quality of public procurement delivery for the socio-economic development of the country. Despite the benefits promised by e-procurement systems, their adoption remains a challenge in the construction industry, especially in comparison to other sectors in developing countries. This study aims to develop a proposed framework that could be adopted to improve the readiness of the construction sector, Small and Medium Enterprises (SMEs) to adopt GHANEPS. The study adopted a qualitative multiple-case study research design. Six cases were purposively selected based on pre-determined criteria. Twenty-eight (28) participants, comprising eighteen (18) respondents from SME construction firms in the Upper West Region and ten (10) public procurement practitioners from Municipal/District assemblies were also purposively selected. Data obtained through the interview guide from the participants were transcribed and analysed using the thematic analysis method. The study found challenges such as inadequate IT infrastructure, limited office space, lack of trained personnel, poor internet connectivity, absence of government contracts, PPA requirement etc. to be inhibiting the readiness of SMEs to adopt GHANEPS. The adoption and implementation of the interventions in the developed framework such as; building robust IT infrastructure, defined roles for staff, recruitment of qualified IT staff, improved internet connectivity and in-service training for personnel, etc. by all stakeholders could mitigate the challenges confronting SMEs in the construction sector.